Integrating Management Auditing with Social and Environmental Accounting: Case studies from the Mining, Financial, and Technology Sectors - Upe, Al Quadhri; Al Asyary; Rahman, Muljibir (Institut Agama Islam Negeri Kendari, 2025)
This study examines the relationship between management auditing and social and environmental accounting in the context of the development of sustainable business practices. It highlights the shift in management auditing from a financial focus to integrating Environmental, Social, and Governance (ESG) principles and social and environmental impacts. Through a systematic literature review of 56 peer-reviewed articles published between 2020-2024. The results show that the integration of social and environmental accounting in management auditing contributes to strengthening corporate governance, mitigating reputational risks, and creating sustainable value. The research also highlights challenges in the implementation of management audits integrated with social and environmental accounting, including standardization of measurement methods, limited auditor competence, and regulatory complexity. This conceptual study is limited by its literature-based approach and requires further empirical validation to test the proposed integrated management audit framework in real-world organizational contexts. The theoretical and practical implications of this research provide insights for academics, audit practitioners, and stakeholders in developing a comprehensive and sustainable management audit framework.